The Influence of Online Prices and Promotions on Purchase Decisions on the Shopee Marketplace (Case Study at PT. Gucci Ratu Textile, Cimahi City, West Java) - Ghea Ocktalissa Maedia; Ayi Muhiban (International Journal of Integrative Sciences, 2023)
This research is motivated by the influence of online prices and promotions on purchasing decisions at the shopee marketplace. The research method used is quantitative with a descriptive and associative approach. With a population of 750 and a total sample of 88 taken using probability sampling technique. The unit of observation in this study is an employee at PT. Gucci Ratu Textile, City of Cimahi, West Java, which conducts online shopping activities on the shopee marketplace. This study uses multiple linear regression analysis as a data analysis technique and has carried out the validity and reliability of the instruments used in the study. The results showed that partially, the price variable had an effect of 75.61% on purchasing decisions at the shopee marketplace, while online promotions had an effect of 22.34%. Overall, online prices and promotions have an effect of 98% on purchasing decisions on the shopee marketplace, while 2% are influenced by other factors not examined in this study